Efficiency in a forced contribution threshold public good game - Edward Cartwright; Anna Stepanova (University of Kent, School of Economics, 2015)
We contrast and compare three ways of predicting efficiency in a forced contribution threshold public good game. The three alternatives are based on ordinal potential, quantal response and impulse balance theory. We report an experiment designed to test the respective predictions and find that impulse balance gives the best predictions. A simple expression detailing when enforced contributions result in high or low efficiency is provided.
Keywords: C72; H41; C92; 330; public good; threshold; impulse balance theory; quantal response; forced contribution; ordinal potential